Adopting evidence-based guidelines for acute stroke care: barriers and enablers for health professionals. (2nd February 2020) - Harrison, Joanna; Timoroksa, Anne-Marie; Gregary, Bindu; Hill, James Edward
Abstract : An evidence summary based on the systematic review: Baatiema L, Otim ME, Mnatzaganian G, de-Graft Aikins A, Coombes J, Somerset S. Health professionals' views on the barriers and enablers to evidence-based practice for acute stroke care: a systematic review. Implement Sci. 2017;12:74. 10.1186/s13012-017-0599-3 Evidence-based practice is the keystone of clinical practice, policy and management. Despite this, a knowledge-to-practice gap still exists, and it is estimated to take 17 years for evidence to be translated into clinical practice. The reasons for slow translation in acute stroke care are not completely understood.